Hydroxyapatite combined with hyaluronic acid metronidazole gel increased the quantity of osteoblasts in the alveolar bone wistar rat - Ernie Maduratna Setiawatie (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Bone graft material have been used extensively in bone healing and periodontal treatment. Alloplast such as hydroxyapatite are frequently used to repair and reconstruct bone defects. By merely applying hydroxyapatite for the treatment of bone is not fully effective yet to produce new bone regeneration. Locally applied high molecular hyaluronic acid (HA) has been shown to stimulate differentiation and migration of mesenchymal cells. Recent studies on regenerative surgical procedures indicate that reduction of bacterial burden at the wound site may improve the clinical outcome of regenerative therapy. Metronidazole has the greatest bacteriostatic effect. A clinical application of HA metronidazole gels during the surgical therapy may reduce the bacterial contamination of surgical wound site. Purpose: The purpose of this study was to examine the effect of combination hydroxyapatite and HA metronidazole gel 1% on osteoblast cell number after wound healing process in the wistar rats incisor tooth extraction socket. Method: Twenty seven wistar rats were divided randomly into 3 groups. The first group consisted of wistar rats given hydroxyapatite were subjected to the mandibular incisor extraction socket. The second group were given hydroxyapatite combined with HA metronidazole gel 1%. The control group were filled with blood. Wistar rats were euthanized on day 14 and then preparation for histological examination was stained using hematoxylin-eosin and then the numbers of the osteoblasts were calculated. Result: The differences in each group were tested by one way Anova test (α=0.05). The numbers of osteoblasts in each group had a significant difference (p<0.05): the highest numbers of osteoblasts were found in the group that was given hydroxyapatite combined with HA metronidazole, followed by the lower numbers of osteoblasts in the hydroxyapa ite group and the lowest numbers of osteoblasts were found in the control group. Conclusion: Adjunctive application of HA metronidazole to hydroxyapatite after tooth extraction increase the number of osteoblast in the treatment of bone defects on a wistar rat model.